FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PENGETAHUAN PEGAWAI PUSKESMAS MENGENAI KESELAMATAN PASIEN DI PUSKESMAS SUKASADA I - Indrayathi, Putu Ayu; Krismayani, Tika (ARCHIVE OF COMMUNITY HEALTH, 2024)
Patient safety is a system that makes patients safer. Patient safety is very important in the era of National Health Insurance (JKN) because it follows a managed care system that requires the community to conduct a level referral from basic health services namely Primary Health Care ( Puskesmas ). This research aims to investigate the factors related to the level of knowledge of Puskesmas officers on the safety of patients at Puskesmas Sukasada I, Buleleng regency. It used descriptive quantitative research design with a cross-sectional study draft. The samples of research involved all the employees who work in the Puskesmas Sukasada I. It was conducted in April 2020. Data were obtained by using the instrument of questionnaires consisting of closed questions to be filled out by respondents. Data analysis were done univariate and bivariate with the chi-square test. The results revealed that 56.00% of respondents had a good level of knowledge of patient safety. There was meaningful relationship among variable of education with knowledge level (p<0.05), while age, gender, work experience and training variables did not have meaningful relationship with knowledge levels (p?0,05). The primary health care is more active in conducting socialization and training on the safety of patients in primary health care. Keywords: Knowledge level , Patients safety , P rimary Health Care , Officers